2004
DOI: 10.1080/00365520410007999
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of the immunoglobulin enhancer HS1,2 allele 2 in coeliac disease

Abstract: Background: Coeliac disease ( CD) is characterized by increased immunological responsiveness to ingested gliadin in genetically predisposed individuals. This genetic predisposition is not completely defined. A dysregulation of immunoglobulins (Ig) is present in CD: since antiendomysium antibodies (anti-EMA) are of the IgA class. One polymorphic enhancer within the locus control region (LCR) of the immunoglobulin heavy chain cluster at the 3' of the C alpha-1 gene was investigated. The correlation of the penetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 17 publications
4
35
1
Order By: Relevance
“…Since our previous observations have shown that the HS1.2 polymorphism is also associated with IgA deficiency23 24 and an association of the HS1.2 allele *2 has been reported with coeliac disease,19 psoriasis and dermatitis herpetiformis20 and with systemic sclerosis21 and rheumatoid arthritis,22 we believe our findings indicate a definite role as a risk factor in autoimmune diseases. These data thus reinforce the relationship of this heavy chain locus control region with autoimmunity.…”
Section: Discussionsupporting
confidence: 67%
“…Since our previous observations have shown that the HS1.2 polymorphism is also associated with IgA deficiency23 24 and an association of the HS1.2 allele *2 has been reported with coeliac disease,19 psoriasis and dermatitis herpetiformis20 and with systemic sclerosis21 and rheumatoid arthritis,22 we believe our findings indicate a definite role as a risk factor in autoimmune diseases. These data thus reinforce the relationship of this heavy chain locus control region with autoimmunity.…”
Section: Discussionsupporting
confidence: 67%
“…Alternatively, and more likely, the presence of a high frequency of allele *1 and low frequency of allele *2, may be associated to a given pattern of immune response characterized by several features: both IGA and IGM production. It has been shown that specular (high allele *2, low allele *1) pattern of HS1.2 allelic distribution is present in diseases with increased or abnormal IgA production such as IgA nephropathy and Celiac disease (30,34). These results expand our knowledge of the possible role of HS1.2 alleles in the regulation of Ig production and in the pathogenesis of human immunological diseases.…”
Section: Discussionmentioning
confidence: 48%
“…However further studies are needed to clarify the role, if any, of HS1.2 allele *1 in the pathogenesis of IGAD and to confirm a pattern of allelic frequencies associated to increased (allele *2 high; allele *1 low) or decreased (allele *1 high; allele *2 low) IgA production. It is also worth noting that IGAD increases susceptibility to celiac disease (34,36). One additional point that can be made based on the results presented herein and those already available of a correlation between allelic frequency and immune mediated diseases is related to the functions of 3ЈRR-1 and 3ЈRR-2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the gene CDKAL 1 on the chromosome 6p22 showed a close relation between CD and psoriasis (18). Other studies revealed an increased frequency of the Ig heavy-chain HS 1,2-A enhancer *2 allele in psoriasis and intestinal inflammatory disease (21)(22) (19,23), with the consequence that the neutralization of endogenous TNF causes pDCs to remain in an immature status with consequent increase in IFN-a secretion and release (19,23). By inducing mDC activation/maturation, IFN-a brings about the differentiation and expansion of Thl cells (19,24).…”
Section: Discussionmentioning
confidence: 99%